Screening for Non-Communicable Diseases and Cardiopulmonary Resucitation Education in Kranjingan Village, Sumbersari District, Jember Regency - Lirista Dyah Ayu Oktafiani; Arina Mufida Ersanti; Ayu Munawaroh Aziz (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
Non-communicable diseases (NCDs) are catastrophic diseases that can cause an increase in the socio-economic burden for sufferers, their families and the government, because their treatment takes a long time, costs a lot and requires high technology. Cardiovascular disease is one of the PTM diseases in Jember Regency which has a high prevalence of cases. Screening activities through posbindu are one of the efforts that can be done to prevent and control PTM. This activity aimed to screen NCDs and improve Cardiopulmonary Resuscitation (CPR) skills in the Kranjingan Village community, Sumbersari District, Jember Regency. This activity was carried out through several stages, starting with counseling, examining early detection of PTM risk factors, counseling and CPR training. Screening activities were important to be carried out to increase public awareness of non-communicable diseases through early detection, early treatment and controlling risk factors so as to reduce morbidity and mortality rates. After this activity, it was known that there has been an increase in participants' knowledge related to Cardiopulmonary Resuscitation (CPR) skills in the community in Kranjingan Village, Sumbersari District, Jember Regency.